(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
A 4G system is expected to provide an all inclusive and secure all-IP based mobile broadband solution to laptop, wireless modems, computer, smart phones, and other mobile devices. Although many studies were conducted in the past, there are still many challenges to be met when resource allocation is to be performed in an optimal manner. In the light of the same, a hybrid approach for optimized resource allocation is proposed in a deployed 4G Long Term Evolution (LTE) network. For this to accomplish, firstly a comparative study of the state-of-the-art models has been performed to find out the most optimal method for resource allocation and then propose a hybrid approach to blend the merits of two or more techniques. So, in this article, four main techniques, namely, Binary Phase Shift Keying modulation (BPSK), Quadrature Phase Shift Keying (QPSK), Quadrature amplitude modulation (QAM), Orthogonal Frequency Division Multiplexing (OFDM), as modulation techniques have been compared. Since, OFDM outperformed the other modulation techniques, so, it has been integrated with QPSK and OFFT to obtain the most optimal resource allocation. Experimental results show that the proposed technique is simple and robust, and quite promising in the near future for deployed 4G LTE networks.